Mobility and regional inequality in the European Union: Implications for economic policy - Roberto Ezcurra; Carlos Gil; Padro Pascual; Manuel Rapun (European Regional Science Association (ERSA), 2002)
The aim of this paper is to analyse the mobility of per capita income distribution in the European regions during the period 1977-1996. In doing so we will attempt highlight some aspects of the nature of interregional inequality. We also hope to draw inferences that might be applied by European regional policy makers. If, for example, there proves to be very little mobility, this might mean that the regional positions are consolidated. If this were the case, a belligerent regional policy could be introduced in order to reduce regional disparities. If, on the other hand, our results suggest that income variability accounts for most of the disparities, regional policy could be focused on the negative effects of economic cycles. In this case, a regional convergence policy might be made to take second place. Our methodological approach involves calculating indices commonly used in the dynamic income distribution literature, such as those of Theil, Atkinson and Shorrocks. These indices are calculated at different levels, both temporal and geographical, in order to discover different regional behaviour patterns throughout the study period.
Keywords: 330